Differential inflammatory networks distinguish responses to bone marrow-derived versus adipose-derived mesenchymal stem cell therapies in vascularized composite allotransplantation. Issue 1 (July 2017) - Zamora, Ruben; Ravuri, Sudheer K.; Plock, Jan A.; Vodovotz, Yoram; Gorantla, Vijay S.
Abstract : BACKGROUND: Vascularized composite allotransplantation (VCA) is aimed at enabling injured individuals to return to their previous lifestyles. Unfortunately, VCA induces an immune/inflammatory response, which mandates lifelong, systemic immunosuppression, with attendant detrimental effects. Mesenchymal stem cells (MSC)—both adipose-derived (AD-MSC) and bone marrow–derived (BM-MSC)—can reprogram inflammation and have been suggested as an alternative to immunosuppression, but their mechanism of action is as yet not fully elucidated. We sought to gain insights into these mechanisms using a systems biology approach. METHODS: PKH26 (red) dye-labeled AD-MSC or BM-MSC were administered intravenously to Lewis rat recipients of mismatched Brown-Norway hindlimb transplants. Short course tacrolimus (FK-506) monotherapy was withdrawn at postoperative day 21. Sera were collected at 4 weeks, 6 weeks, and 18 weeks; assayed for 29 inflammatory/immune mediators; and the resultant data were analyzed using Dynamic Network Analysis (DyNA), Dynamic Bayesian Network (DyBN) inference, and Principal Component Analysis. RESULTS: DyNA network complexity decreased with time in AD-MSC rats, but increased in BM-MSC rats. DyBN and Principal Component Analysis suggested mostly different central nodes and principal characteristics, respectively, in AD-MSC versus BM-MSC rats. CONCLUSION: AD-MSC and BM-MSC are associated with both overlapping and distinct dynamic networks and principal characteristics of inflammatory/immune mediators in VCA grafts with short-course tacrolimus induction therapy. The decreasing inflammatory complexity of dynamic networks in the presence of AD-MSC supports the previously suggested role for T regulatory cells induced by AD-MSC. The finding of some overlapping and some distinct central nodes and principal characteristics suggests the role of key mediators in the response to VCA in general, as well as potentially differential roles for other mediators ascribed to the actions of the different MSC populations. Thus, combined in vivo/in silico strategies may yield novel means of optimizing MSC therapy for VCA. Abstract : Supplemental digital content is available in the text.